Labour's Immigration Policy The Making of the Migration State - Consterdine, Erica (Springer International Publishing, 2018)
This book explains how and why the New Labour governments transformed Britain's immigration system from a highly restrictive regime to one of the most expansive in Europe, otherwise known as the Managed Migration policy. It offers the first in-depth and candid account of this period of dramatic political development from the actors who made policy during 'the making of the migrant state.' Drawing on document analysis and over 50 elite interviews, the book sets out to explain how and why this radical policy change transpired, by examining how organized interests, political parties and institutions shaped and changed policy. This book offers valuable insights to anyone who wants to understand why immigration is dominating the political debate, and will be essential reading for those wanting to know why governments pursue expansive immigration regimes.